The Relationship between Corporate Social Responsibility and Financial Performance Across Cultures - Bhasin, Surbhi (2009)
The research on the relationship between Corporate Social Responsibility (CSR) and financial performance has been carried out in various geographical locations and various parameters for defining proxies for CSR and financial performance has been used. But there were lots of constraints and contingencies due to various proxies used for financial performance, multi industry analysis and variations and inconsistency in data selection, methodology (Karake, 1999). Using data over the time period of four years, this study investigate and examine the link between corporate social responsibility and financial performance across cultures. The clusters included in this study are Asia, Europe and UK/US. Two studies are conducted, first comprise of the single industry study of automobile concerns across the globe based on their ethical rankings and cover the years 2005-2008.The second study take into account the differences in the level of CSR across 3 clusters and its link with financial performance in multi-industry concern. The relationship is analysed by means of empirical techniques using ANOVA, t-test and regression analysis. The outcomes are that the companies of UK-US clusters show highest involvement in the CSR activities followed by Europe and then Asia. A mixed relationship was established between CSR and FP across all the clusters. UK-US showed highest positive relationship between the CSR and the financial performance. In our study, it was discovered that with the change of proxies for CSR and FP, the relationship established also changes.